Cement paste system capable of self-healing when meeting carbon dioxide and used for well cementation as well as preparation method and application of cement paste system

By adding carbon dioxide self-healing agent to cement cement slurry, the self-healing function of cement slurry is achieved, and the problem of lack of self-healing performance of existing cement slurry is solved, and the sealing performance of cement rings and the service life of the oil well is improved.

CN119569375AActive Publication Date: 2025-03-07CHINA NAT PETROLEUM CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202410477814.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-03-07
Estimated Expiration
2044-04-19

AI Technical Summary

Technical Problem

The existing cement slurry system for cementing lacks self-healing performance and cannot automatically seal the microcracks or micro gaps generated by the cement ring, resulting in a degradation of sealing performance and affecting the life of the oil and gas well and production safety.

Method used

A cement slurry system for self-healing with carbon dioxide is developed to cement the cement slurry. By adding a carbon dioxide self-healing agent to the cement slurry, the volume of the self-healing agent is expanded by the stimulating effect of carbon dioxide, and the micro-cracks or micro-gaps are automatically blocked.

Benefits of technology

The cement slurry system has excellent corrosion resistance, self-healing, toughness and anti-trapped properties, which can effectively seal microcracks or micro gaps, improve the sealing performance of cement rings, and extend the service life of the oil well.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004800997620000031
    Figure BDA0004800997620000031
  • Figure BDA0004800997620000101
    Figure BDA0004800997620000101
  • Figure BDA0004800997620000111
    Figure BDA0004800997620000111
Patent Text Reader

Abstract

The invention provides a cement paste system capable of self-healing when meeting carbon dioxide for well cementation as well as a preparation method and application of the cement paste system. The cement paste system comprises oil well cement, a carbon dioxide self-healing agent, silicon dioxide, an anticorrosive agent and water, as the carbon dioxide self-healing agent is added into a cement paste system, when a cement sheath has micro-cracks or micro-gaps and carbon dioxide fluid channeling is generated, the carbon dioxide self-healing agent expands in volume under the stimulation action of carbon dioxide, and the micro-cracks or micro-gaps are automatically blocked, so that the purposes of inhibiting carbon dioxide fluid channeling and preventing carbon dioxide fluid channeling are achieved. The effect that the cement sheath continuously has excellent packing performance is ensured; and meanwhile, the carbon dioxide self-healing agent has good compatibility in a cement slurry system, so that the finally obtained cement slurry system has excellent corrosion resistance, self-healing property, toughness and channeling resistance, is suitable for a temperature interval of 30-100 DEG C, and can be used for well cementation of carbon flooding and burying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oilfield development, and in particular relates to a cement slurry system for well cementing which is self-healing when exposed to carbon dioxide, and a preparation method and application thereof. Background Art

[0002] Cementing operations are an important part of the oilfield development process, and the performance of cement slurry has a crucial impact on the quality of cementing. In the process of oilfield development, due to the complex and changeable formation conditions, higher requirements are placed on the cement slurry system, which requires it to have excellent anti-corrosion performance, toughness, anti-channeling performance, and self-healing performance when exposed to gas. However, since the cement ring formed by the cement slurry system is a brittle material, it is very easy to be damaged and cracked under the action of external forces, which can easily cause oil and gas channeling during cementing operations. In severe cases, it will cause annular pressure or wellhead gas emission, affecting the life of oil and gas wells and production safety. Therefore, the development of a cement slurry system with excellent anti-corrosion performance, toughness, anti-channeling performance, and self-healing performance when exposed to gas has always been the focus of research in this field.

[0003] At present, there are many cement slurry systems reported for cementing. CN112939527A discloses an ultra-high strength and toughness cement slurry system for cementing, and its preparation and application. The raw material composition of the ultra-high strength and toughness cement slurry system for cementing includes: 100 parts by weight of cement, 20 to 40 parts by weight of high temperature reinforcing material, 0.5 to 6 parts by weight of inorganic toughening material, 0.5 to 4 parts by weight of suspension stabilizer, 2 to 6 parts by weight of microsilicon, 0.5 to 1.5 parts by weight of dispersant, 2 to 6 parts by weight of fluid loss reducer, 1 to 8 parts by weight of retarder, 0.2 to 1 parts by weight of defoamer and 40 to 60 parts by weight of clean water; the cement slurry system has the advantages of good fluidity and sedimentation stability, low water loss, adjustable thickening time, and wide temperature range.

[0004] However, the cement slurry system including the above invention does not have self-healing properties, and cannot automatically seal the internal microcracks or microgaps generated when the brittle cement ring is damaged by external forces. It is impossible to ensure that the cement ring maintains excellent sealing performance, which will seriously affect the life of oil and gas wells and production safety.

[0005] Therefore, in order to solve the above technical problems, developing a cement slurry system with self-healing properties for cementing and self-healing in the presence of carbon dioxide is still a technical problem that needs to be urgently solved in this field. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a cement slurry system for cementing that is self-healing in the presence of carbon dioxide and its preparation method and application. The cement slurry system has excellent corrosion resistance, self-healing, toughness and anti-channeling properties, can meet the needs of oil field cementing operations, improve cementing quality, and extend the service life of oil wells. It is particularly suitable for carbon flooding, utilization and burial wells. To achieve this purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a cement slurry system for well cementing that is self-healing in the presence of carbon dioxide. The cement slurry system comprises oil well cement, a self-healing agent in the presence of carbon dioxide, silicon dioxide, a corrosion inhibitor and water.

[0008] The carbon dioxide self-healing cement slurry system for cementing provided by the present invention comprises oil well cement, carbon dioxide self-healing agent, silicon dioxide, corrosion inhibitor and water; since the carbon dioxide self-healing agent is added to the cement slurry system, when microcracks or microgaps appear in the cement ring formed by the cement slurry system after the cementing operation and carbon dioxide crossflow is generated, the carbon dioxide self-healing agent will expand in volume under the stimulation of carbon dioxide, and automatically block the generated microcracks or microgaps, so as to achieve the effect of inhibiting carbon dioxide crossflow, thereby ensuring that the cement ring can always have excellent sealing performance; in addition, the carbon dioxide self-healing agent has good compatibility with other components of the cement slurry system, and there is no need to change the construction process and equipment. The construction process is the same as that of the conventional cement slurry system, and finally the obtained cement slurry system can have excellent corrosion resistance, self-healing property, toughness and anti-crossflow property, and is suitable for cementing of carbon dioxide flooding and storage (CCUS) in the temperature range of 30 to 100°C.

[0009] Preferably, the cement slurry system comprises the following components in parts by weight:

[0010]

[0011]

[0012] In the present invention, the amount of oil well cement in the cement slurry system is 100 parts by weight.

[0013] In the present invention, the amount of the self-healing agent when exposed to carbon dioxide is 5 to 30 parts by weight, for example, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight or 30 parts by weight, and specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0014] In the present invention, the amount of silicon dioxide is 0.5 to 60 parts by weight, for example, 0.5 parts by weight, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or 50 parts by weight, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0015] In the present invention, the amount of the corrosion inhibitor is 0.5 to 20 parts by weight, for example, 0.5 parts by weight, 2 parts by weight, 5 parts by weight, 8 parts by weight, 12 parts by weight, 16 parts by weight or 20 parts by weight, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0016] In the present invention, the amount of water is 40 to 100 parts by weight, for example, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight or 100 parts by weight, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0017] Preferably, the oil well cement is Grade G oil well cement.

[0018] Preferably, the self-healing agent when exposed to carbon dioxide includes any one of calcium oxide whiskers, carbon nanotubes, graphite oxide or polymer polyols, or a combination of at least two of them; the combinations include but are not limited to: a combination of calcium oxide whiskers and carbon nanotubes, a combination of carbon nanotubes and graphite oxide, a combination of carbon nanotubes and polymer polyols, a combination of carbon nanotubes, calcium oxide whiskers and polymer polyols, and the like.

[0019] Among them, the calcium oxide whiskers can generate rod-shaped calcium carbonate when encountering carbon dioxide, thereby playing a filling and supporting role; the carbon nanotubes and graphite oxide can adsorb carbon dioxide to cause the material to expand, thereby playing a filling and supporting role; the polymer polyol can generate polyurethane resin when encountering carbon dioxide, produce an adhesive structure, promote the re-bonding of cement cracks, and achieve a sealing effect.

[0020] Preferably, the D of the calcium oxide whisker is 50 The particle size is 10 to 80 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm or 80 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0021] Preferably, the carbon nanotubes have a D 50The particle size is 10 to 100 μm, for example, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm or 100 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0022] Preferably, the D of the graphite oxide 50 The particle size is 100 to 500 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0023] It should be noted that the present invention has no special requirements and restrictions on the specific type and molecular weight of the polymer polyol, as long as it can react with carbon dioxide to form an adhesive structure. However, in order to achieve the best sealing effect, preferably, the polymer polyol includes a vinyl polymer grafted polyether polyol.

[0024] Preferably, the silicon dioxide comprises any one of silicon powder, micro silicon or nano silicon, or a combination of at least two of them.

[0025] Preferably, the D of the micro-silicon 50 The particle size is 1 to 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0026] Preferably, the D of the nano-silicon 50 The particle size is 100 to 300 nm, for example 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm or 300 nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0027] Preferably, the silicon powder has a D 50 The particle size is ≥50μm, for example, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm or 90μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0028] Preferably, the corrosion inhibitor includes any one of dispersible latex powder, high temperature resistant resin, slag powder or volcanic ash, or a combination of at least two thereof; wherein the high temperature resistant resin refers to a resin that can withstand a high temperature of 150°C.

[0029] Preferably, the cement slurry system further includes other functional admixtures, and specifically, weighting materials or lightening materials may be added according to actual cementing requirements.

[0030] Preferably, the other functional admixtures include any one of a toughening agent, an anti-gas channeling agent, a swelling agent, a fluid loss reducer, a dispersant, a setting regulator, a reinforcing agent or a defoaming agent, or a combination of at least two thereof.

[0031] Preferably, based on 100 parts by weight of the oil well cement, the amount of the toughening agent is 0.1 to 5 parts by weight, for example, 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0032] Preferably, based on 100 parts by weight of the oil well cement, the amount of the anti-gas channeling agent is 0.5 to 5 parts by weight, for example, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight or 5 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0033] Preferably, based on 100 parts by weight of the oil well cement, the amount of the expansion agent is 0.1 to 3 parts by weight, for example, 0.1 parts by weight, 0.5 parts by weight, 1 parts by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight or 3 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0034] Preferably, based on 100 parts by weight of the oil well cement, the amount of the fluid loss reducer is 0.5 to 3 parts by weight, for example, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight or 3 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0035] Preferably, based on 100 parts by weight of the oil well cement, the amount of the dispersant is 0.1 to 2 parts by weight, for example, 0.1 parts by weight, 0.3 parts by weight, 0.6 parts by weight, 0.9 parts by weight, 1.1 parts by weight, 1.3 parts by weight, 1.5 parts by weight, 1.7 parts by weight, 1.9 parts by weight or 2 parts by weight, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0036] Preferably, based on 100 parts by weight of the oil well cement, the content of the setting regulator is 0.5 to 4 parts by weight, for example, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight or 4 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0037] Preferably, based on 100 parts by weight of the oil well cement, the amount of the enhancer is 0.5 to 10 parts by weight, for example, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 4 parts by weight, 6 parts by weight, 8 parts by weight or 10 parts by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0038] Preferably, based on 100 parts by weight of the oil well cement, the amount of the defoaming agent is 0.1 to 1 part by weight, for example, 0.1 part by weight, 0.2 part by weight, 0.4 part by weight, 0.6 part by weight, 0.8 part by weight or 1 part by weight, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0039] In the present invention, there is no special restriction on the specific types of the above-mentioned other functional admixtures. However, in order to ensure that the obtained cement slurry system has the best corrosion resistance, self-healing property, toughness and anti-channeling property, the types of the above-mentioned other functional admixtures are preferably selected as follows:

[0040] Preferably, the toughening agent comprises GWI-100S and / or GWI-200S.

[0041] Preferably, the anti-gas channeling agent includes any one of GWT-100S, GWT-200S or GWT-300S.

[0042] Preferably, the expansion agent includes any one of GWP-1S or GWP-100S.

[0043] Preferably, the fluid loss additive includes any one of GWF-200L, GWF-200S or GWF-120S.

[0044] Preferably, the dispersant includes any one of GWD-1S, GWD-1L or GWD-100L.

[0045] Preferably, the setting regulator includes any one of GWA-1S, GWA-2S, GWR-100L, GWR-200L, GWR-300L or GWR-310L.

[0046] Preferably, the enhancer includes any one of GWB-1S, GWB-2S, GWB-3S or GWB-100S.

[0047] Preferably, the defoaming agent comprises GWX-1L and / or GWX-2L.

[0048] Preferably, the density of the cement slurry system is 1.80-1.90 g / cm 3 , for example 1.82 g / cm 3 、1.84g / cm 3 , 1.86g / cm 3 or 1.88 g / cm 3 , and specific point values ​​between the above point values. Due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0049] Preferably, the cement paste formed by the cement slurry system has a permeability growth rate of ≤15% and a strength decay rate of ≤20% within 60 days under carbon dioxide curing.

[0050] Preferably, the cement stone formed by the cement slurry system has a permeability reduction rate of ≥30% after being broken under carbon dioxide curing for 60 days.

[0051] Preferably, the 7-day elastic modulus of the cement stone formed by the cement slurry system is less than 6.0 GPa.

[0052] Preferably, the static gelling transition time of the cement slurry system is less than 30 min.

[0053] Preferably, the thickening transition time of the cement slurry system is less than 30 min.

[0054] Preferably, the 24h cement paste compressive strength of the cement slurry system is greater than 16MPa, and the 48h cement paste compressive strength is greater than 24MPa.

[0055] Preferably, the 7-day linear expansion rate of the cement slurry system is 0-0.2%.

[0056] In a second aspect, the present invention provides a method for preparing a cement slurry system that self-heals when exposed to carbon dioxide for cementing as described in the first aspect, the preparation method comprising: uniformly mixing oil well cement, a self-healing agent when exposed to carbon dioxide, silica, a corrosion inhibitor and water, and optionally adding other functional admixtures for mixing to obtain the cement slurry system.

[0057] In a third aspect, the present invention provides an application of the cement slurry system for cementing that self-heals when exposed to carbon dioxide as described in the first aspect in the development of carbon oil fields.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) The carbon dioxide self-healing cement slurry system provided by the present invention has excellent corrosion resistance, self-healing, toughness and anti-channeling properties, which can meet the needs of oil field cementing operations, improve cementing quality and extend the service life of oil wells;

[0060] (2) The self-healing speed of the cement slurry system for cementing provided by the present invention is fast when exposed to carbon dioxide, and the micro cracks or micro gaps generated by the cement sheath can be effectively blocked within 5 to 10 minutes;

[0061] (3) The self-healing agent in the presence of carbon dioxide added to the cement slurry system for cementing provided by the present invention can be fully dispersed in the cement, so that the obtained cement slurry has good stability and good compatibility with other components. There is no need to change the construction process and equipment, and the construction process is the same as that of the conventional cement slurry system. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] The following specific implementation methods involve some raw material information as follows:

[0064] Calcium oxide whiskers: D 50 Particle size: 50 μm;

[0065] Carbon nanotubes: 50 Particle size: 80 μm;

[0066] Graphite oxide: its D 50 Particle size is 200nm;

[0067] Polymer polyol: specifically vinyl polymer grafted polyether polyol, purchased from Shandong Huayou Wanda Chemical Co., Ltd.;

[0068] Microsilicon: Its D 50 Particle size: 5 μm;

[0069] Nano silicon: its D 50 Particle size is 200nm;

[0070] Silicon powder: D 50 Particle size: 60 μm;

[0071] Dispersible latex powder: specifically solid styrene-butadiene latex toughening agent powder, purchased from Rizhao Kumho Jinma Chemical Co., Ltd., brand name GPL-S1;

[0072] High temperature resistant resin: purchased from Shandong Huayou Wanda Chemical Co., Ltd.;

[0073] Slag powder: specific surface area ≥400m 2 / kg, activity index A3 reached about 48%, A28 reached more than 98%;

[0074] Volcanic ash: specifically a new type of ultra-fine volcanic ash powder material, purchased from Beijing Zhengyuan Yiqing Materials Co., Ltd., brand MS1250;

[0075] Toughening agent: specifically GWI-100S;

[0076] Anti-gas channeling agent: specifically GWT-100S;

[0077] Expansion agent: specifically GWP-1S;

[0078] Fluid loss reducer: specifically GWF-200L;

[0079] Dispersant: specifically GWD-1S;

[0080] Coagulant: specifically GWA-1S;

[0081] Enhancer: specifically GWB-1S;

[0082] Defoaming agent: specifically GWX-1L.

[0083] Examples 1 to 9 and Comparative Example 1

[0084] Examples 1 to 9 and Comparative Example 1 respectively provide a cement slurry system for cementing that is self-healing when exposed to carbon dioxide. Comparative Example 1 provides a cement slurry system, and the components and amounts thereof are shown in Table 1. The units of the amounts of the components in Table 1 are all "g".

[0085] Table 1

[0086]

[0087]

[0088] The preparation method of the cement slurry system provided in Examples 1 to 9 and Comparative Example 1 includes: uniformly mixing G-grade oil well cement, self-healing agent in contact with carbon dioxide, silicon dioxide, corrosion inhibitor and water, adding other functional admixtures and mixing to obtain the cement slurry system.

[0089] Performance Testing:

[0090] (1) The basic properties of the cement slurry systems provided in Examples 1 to 9 and Comparative Example 1 were tested, and the test methods and test results are summarized in Table 2;

[0091] Table 2

[0092]

[0093] According to the data in Table 2, we can conclude that:

[0094] The cement slurry systems provided in Examples 1 to 9 all have good basic performance, and their anti-gas channeling properties are qualified. The 7-day linear expansion rate is 0.06-0.17%. At the same time, the 24h compressive strength is as high as 16.4-25.3MPa, and the 48h compressive strength is as high as 24.6-31.9MPa. However, the cement slurry system provided in Comparative Example 1 does not contain any carbon dioxide self-healing agent, and thus has unqualified anti-gas channeling properties. The 7-day linear expansion rate is -0.05%, indicating that not only no expansion but even contraction has occurred. At the same time, the 24h compressive strength is only 14.4MPa, and the 48h compressive strength is only 21.7MPa.

[0095] (2) The self-healing and anti-corrosion properties of the cement slurry systems provided in Examples 1 to 9 and Comparative Example 1 were tested, and the test methods and test results are summarized in Table 3;

[0096] Table 3

[0097]

[0098] According to the data in Table 3, it can be seen that the cement slurry systems provided in Examples 1 to 9 also have excellent corrosion resistance and self-healing properties. Among them, the corrosion resistance test shows that the 60-day permeability growth rate is only 8.8-12.9%, and the 60-day strength attenuation rate is only 12.2-17.4%. The self-healing test shows that the self-healing permeability reduction rate is as high as 31.4-34.4%. The cement slurry system provided in Comparative Example 1 does not have self-healing properties because no self-healing agent is added when exposed to carbon dioxide, and thus has poor corrosion resistance.

[0099] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a self-healing cement slurry system for cementing in the presence of carbon dioxide and its preparation method and application, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A cement slurry system for well cementing that is self-healing when exposed to carbon dioxide, characterized in that: The cement slurry system comprises oil well cement, a self-healing agent in the presence of carbon dioxide, silicon dioxide, a corrosion inhibitor and water.

2. The cement slurry system according to claim 1, characterized in that: The cement slurry system comprises the following components in parts by weight:

3. The cement slurry system according to claim 1 or 2, characterized in that: The oil well cement is Grade G oil well cement.

4. The cement slurry system according to any one of claims 1 to 3, characterized in that: The carbon dioxide-induced self-healing agent comprises any one of calcium oxide whiskers, carbon nanotubes, graphite oxide or polymer polyols, or a combination of at least two thereof; Preferably, the D of the calcium oxide whisker is 50 Particle size is 10-80 μm; Preferably, the carbon nanotubes have a D 50 Particle size is 10-100 μm; Preferably, the D of the graphite oxide 50 Particle size is 100~500nm; Preferably, the polymer polyol comprises a vinyl polymer grafted polyether polyol.

5. The cement slurry system according to any one of claims 1 to 4, characterized in that: The silicon dioxide includes any one of silicon powder, micro silicon or nano silicon, or a combination of at least two of them.

6. The cement slurry system according to any one of claims 1 to 5, characterized in that: The anticorrosive agent includes any one of dispersible latex powder, high temperature resistant resin, slag powder or volcanic ash, or a combination of at least two of them.

7. The cement slurry system according to any one of claims 1 to 6, characterized in that: The cement slurry system also includes other functional admixtures; Preferably, the other functional admixtures include any one of a toughening agent, an anti-gas channeling agent, a swelling agent, a fluid loss reducer, a dispersant, a setting regulator, a reinforcing agent or a defoaming agent, or a combination of at least two thereof.

8. The cement slurry system according to any one of claims 1 to 7, characterized in that: The density of the cement slurry system is 1.80-1.90 g / cm 3 .

9. A method for preparing a cement slurry system for well cementing that is self-healing when exposed to carbon dioxide as claimed in any one of claims 1 to 8, characterized in that: The preparation method comprises: uniformly mixing oil well cement, a self-healing agent in the presence of carbon dioxide, silicon dioxide, an anticorrosive agent and water, and adding other optional functional admixtures for mixing to obtain the cement slurry system.

10. An application of a cement slurry system for well cementing that is self-healing when exposed to carbon dioxide as claimed in any one of claims 1 to 8, characterized in that: The application includes cementing engineering for oil and gas field development containing carbon dioxide or carbon dioxide utilization and storage wells.

Citation Information

Patent Citations

  • Ultrahigh-strength tough cement paste system for well cementation as well as preparation and application thereof

    CN112939527A

  • Oil-well cement additive against carbon dioxide corrosion as well as preparation method and application thereof

    CN102010702A

  • Well-cementing and self-healing cement slurry for oil-gas field

    CN102746836A

  • Production and application method of oil (water) well channeling and leakage plugging system

    CN106082807A

  • Oil gas-responsive active self-repairing cement slurry system

    CN109180084A